A Catalytic and Shape‐Memory Polymer Reactor. (23rd May 2014) - Han, Yanli; Yuan, Xinhua; Zhu, Maiyong; Li, Songjun; Whitcombe, Michael J.; Piletsky, Sergey A.
<x xml:space="preserve">Abstract</x> An originally designed catalytic and shape‐memory polymer reactor is reported. This reactor is made of a unique shape‐switchable polymer composed of a thermosensitive control layer and an inert substrate layer. With the inert substrate layer made of poly(acrylamide), the thermosensitive control layer consists of nickel nanoparticles and a smart polymer composite of poly(1‐vinylimidazole) (PVIm) and poly(acrylic acid) (PAAc) that exhibit switchable domains. The self‐healing and dissociation between PVIm and PAAc induce convex/concave‐switchable shapes in the resulting reactor, which cause tunable access to the encapsulated metal nanoparticles. In this way, this reactor demonstrates tunable catalytic ability. Unlike reported smart polymer reactors exhibiting tunable catalysis usually due to the thermal phase transition of poly(N‐isopropylacrylamide) (PNIPAm), this novel reactor adopts the shape‐switchable strategy for tunable catalysis. This novel design suggests a new protocol for the development of smart catalytic reactors, which opens new opportunities for controlled chemical processes.